Self-powered ammonia gas monitoring system

The Ga2O3/Ti3C2Tx sensor system powered by TENG solves the flexibility of ammonia leakage monitoring in the chlorammonium industry, and realizes high sensitivity and fast response ammonia sensing, ensuring production safety and efficiency.

CN119310147APending Publication Date: 2025-01-14CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411465483.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing intelligent monitoring system of green ammonia industrial cannot flexibly design the sensor location, resulting in the inability to monitor ammonia leakage in real time, affecting production safety and efficiency.

Method used

The Ga2O3/Ti3C2Tx sensor system powered by TENG is used to realize real-time acquisition and display of ammonia concentration through the rectifying and bucking module energy storage capacitor, voltage management unit, microcontroller unit, wireless transmission module and display module.

Benefits of technology

Achieve high sensitivity, fast response and high durability ammonia sensing, which can quickly detect and locate ammonia leakage, ensure production safety and provide self-powered solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119310147A_ABST
    Figure CN119310147A_ABST
Patent Text Reader

Abstract

The invention provides a self-powered ammonia gas monitoring system, which relates to an intelligent control technology and comprises a TENG, a rectification and voltage reduction module, an energy storage capacitor, a voltage management unit, an MCU, a Ga2O3 / Ti3C2Tx sensor, a wireless transmitting module and a display module, an alternating current generated by the TENG is converted into a direct current through the rectification and voltage reduction module, the voltage management unit transmits the electric energy stored in the energy storage capacitor to the MCU, the Ga2O3 / Ti3C2Tx sensor, the wireless transmitting module and the display module, and the ammonia concentration acquired by the Ga2O3 / Ti3C2Tx sensor is processed by the MCU and then is transmitted to the display module through the wireless transmitting module. According to the technical scheme, the problem that in the prior art, a green ammonia industry intelligent monitoring system cannot flexibly design the position of a sensor according to a use scene, and then ammonia gas leakage cannot be monitored in real time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of intelligent control technology, and in particular to a self-powered ammonia monitoring system. Background Art

[0002] Green ammonia has become an important part of the global new clean energy supply system with its advantages of high energy storage density and combustion calorific value. With the increasing market demand and the ever-increasing application scenarios, the safety and production efficiency of the green ammonia industry have received more and more attention. With the continuous advancement of industrial intelligent technology, the intelligent monitoring system based on multi-sensor nodes has become a feasible solution for preventing gas (ammonia) leakage in the production process and supervising the operation status of equipment. Through real-time and continuous acquisition of industrial process information, the production safety and efficiency of green ammonia are effectively guaranteed. However, in the actual deployment process, the power supply and maintenance of these sensor nodes need to be considered. Because hundreds of wiring power supplies or battery power supplies will not only bring cumbersome design problems, but also cause potential environmental pollution. This greatly restricts the prospects for its practical application. Therefore, how to design flexible and self-driven green ammonia industrial process intelligent monitoring technology for usage scenarios to achieve in-situ gas leakage and production status monitoring has become an urgent problem to promote the sustainable development of the green ammonia industry.

[0003] The triboelectric nanogenerator (TENG) has become an important power supply strategy for the widespread deployment of IoT nodes due to its advantages of low cost, small size, high power density, and environmentally friendly manufacturing materials. In addition, TENG has good compatibility with high-precision micro-nano gas sensors. Unlike traditional electrochemical sensors, micro-nano sensors indicate changes in the concentration of the measured gas through changes in resistance caused by the adsorption and desorption of gas molecules and sensitive materials on their surfaces. The new detection mechanism allows it to not only be directly connected to TENG for power supply, but also to respond quickly to low concentrations of ammonia (ppm level). MXene materials have attracted widespread attention due to their advantages such as high specific surface area and multiple reaction sites. At the same time, gallium oxide has excellent performance in energy storage, catalysis and other fields due to its high bandgap and unique electronic properties. It is expected to compound gallium oxide and MXene binary materials, and use the advantages of both to achieve synergistic effects for highly sensitive ammonia sensing. The circular electrode designed with MEMs technology can also increase the contact area of ​​the sensitive material on the unit electrode, realizing the miniaturization and flexibility of the sensor while maintaining a higher level of accuracy. This is expected to bring a feasible technical solution for in-situ self-driven monitoring.

[0004] Therefore, there is a need for a self-powered ammonia monitoring system. Summary of the invention

[0005] The main purpose of the present invention is to provide a self-powered ammonia monitoring system to solve the problem that the green ammonia industrial intelligent monitoring system in the prior art cannot flexibly design the sensor position according to the usage scenario, and thus cannot perform real-time monitoring of ammonia leakage.

[0006] To achieve the above objectives, the present invention provides a self-powered ammonia monitoring system, comprising: TENG, a rectification and step-down module, an energy storage capacitor, a voltage management unit, a microcontroller unit MCU, a Ga2O3 / Ti3C2Tx sensor, a wireless transmission module and a display module; through the rectification and step-down module, the alternating current generated by the TENG is converted into direct current and stored in the energy storage capacitor. When the capacitor voltage reaches a set value, the voltage management unit transmits the electric energy stored in the energy storage capacitor to the microcontroller unit MCU, the Ga2O3 / Ti3C2Tx sensor, the wireless transmission module and the display module. The ammonia concentration collected by the Ga2O3 / Ti3C2Tx sensor is processed by the microcontroller unit MCU and then transmitted to the display module through the wireless transmission module. The display module displays the ammonia concentration.

[0007] Furthermore, the preparation process of the Ga2O3 / Ti3C2Tx sensor includes preparing Ga2O3 powder, specifically including the following steps: S1, dissolving 0.1 mol of Ga(NO3)3·xH2O in 320 ml of distilled water and stirring evenly with a magnetic stirrer, then adding NH4OH and adjusting the pH value to 9.

[0008] S2, adding the solution obtained in step S1 into a high-pressure reactor and heating it in a muffle furnace at 100° C. for 5 hours; after the reactor is naturally cooled to room temperature, washing the obtained white precipitate with distilled water and ethanol for several times.

[0009] S3, the washed precipitate was dispersed in 5 ml of distilled water and dried in a hot air oven at 75° C. for 8 h.

[0010] S4, placing the obtained pure GaOOH powder sample in a tube furnace and calcining it at 1000°C for 5 h to obtain white Ga2O3 powder.

[0011] Furthermore, the Ga2O3 / Ti3C2Tx sensor preparation process also includes etching Ti3AlC2 MAX with a mixed solution of hydrochloric acid HCl and lithium fluoride LiF to obtain Ti3C2Tx, which specifically includes the following steps: S5, 2 g of LiF and 40 mL of 9 mol HCl were mixed in a PTEF beaker and stirred at 400 rpm for 30 minutes.

[0012] S6, add 2g Ti3AlC2 to the etching solution, then place it in an ice bath for 5min, take the reaction mixture out of the ice bath, reaction temperature 35°C, reaction time 24h, centrifuge at 3500rpm for 10min to obtain a precipitate.

[0013] S7, repeatedly wash the precipitate with deionized water until the pH value of the supernatant after centrifugation is 5.

[0014] S8, adding ethanol and Ga2O3 powder 3 times the mass of Ti3C2Tx to the reaction precipitate, using the dispersion for ultrasonic treatment for 1 hour, centrifuging at 10000 rpm for 10 minutes, and then using deionized water for ultrasonic treatment for 20 minutes to obtain the precipitate.

[0015] S9, 1 ml of the supernatant was filtered with a polyvinylidene fluoride (PVDF) membrane and vacuum dried in a vacuum drying oven at 80° C. for 8 h to obtain the composite Ga2O3 / Ti3C2Tx.

[0016] Furthermore, the Ga2O3 / Ti3C2Tx sensor preparation process also includes the following steps: S10, the Ga2O3 / Ti3C2Tx solution was dropped onto the FR4 substrate, a sensing film was formed by interdigital electrode IDE, and then the Ga2O3 / Ti3C2Tx sensor was obtained after vacuum drying at 60 °C for 4 h.

[0017] Furthermore, TENG is cylindrical, including: a stator and a rotor, the diameter of the cylindrical rotor is smaller than that of the cylindrical stator, and the stator is sleeved on the outside of the rotor, and the rotor rotates relative to the stator.

[0018] Furthermore, the rotor includes: a first acrylic shell, a finger electrode covering the outer side of the first acrylic shell and a Capton film covering the finger electrode, the finger electrode is covered with the Capton film as a friction electric layer, the finger electrode includes: a plurality of first copper electrode layers and a plurality of second copper electrode layers, the first copper electrode layer and the second copper electrode layer are crossed to form the finger electrode, and the first copper electrode layer and the second copper electrode layer extend along the length direction of the acrylic shell.

[0019] Furthermore, the stator includes: a second acrylic shell and multiple grid-shaped copper electrodes covering the inner surface of the second acrylic. The stator has multiple copper electrodes, and two adjacent copper electrodes on the stator are spaced a certain distance apart to form grid-shaped copper electrodes. The copper electrodes on the stator extend along the length direction of the second acrylic shell.

[0020] Furthermore, there are six copper electrodes on the first copper electrode layer, the second copper electrode layer and the stator.

[0021] Furthermore, in the initial state, the copper electrode on the stator is aligned with the copper electrode on the left side of the rotor; due to the difference in electronegativity, electrons are transferred from the surface of the copper electrode on the stator to the surface of the Capton film, and equal amounts of positive and negative charges are generated on the copper electrode on the stator and the surface of the Capton film, respectively. At this time, the TENG is in an electrostatic equilibrium state, and no free electrons flow through the external circuit; as the rotor rotates, the overlapping area between the copper electrode on the stator and the copper electrode on the left side of the rotor decreases, and the potential difference drives the current from the copper electrode on the right side of the rotor to the copper electrode on the left side of the rotor, thereby achieving a new electrostatic equilibrium, and the charge transfer process will continue until the copper electrode on the stator is completely aligned with the copper electrode on the right side of the rotor, at which time the current in the circuit is 0; when the rotor continues to rotate, the overlapping area between the copper electrode on the stator and the copper electrode on the left side of the rotor gradually increases, generating a reverse current until the top copper electrode is completely aligned with the left electrode, thereby generating an AC current signal.

[0022] The present invention has the following beneficial effects: First, the present invention prepares a Ga2O3 / MXene composite material and manufactures an ammonia sensor with high sensitivity (65.7%@2ppm), fast response (5s@2ppm) and high durability (greater than 60 days). By integrating an ammonia sensor and displaying the ammonia concentration in real time, rapid detection and positioning of ammonia leaks can be achieved, so that emergency measures can be taken in time to avoid accidents. Secondly, the present invention uses TENG to directly power the Ga2O3 / Ti3C2Tx sensor. When the sensor switches between 0ppm and 3ppm ammonia environments, the voltage value on the sensor changes. This provides a solution for self-powered ammonia sensing. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the specific implementation of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the specific implementation or the prior art description. Obviously, the drawings described below are some implementations of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings: Figure 1 The flowchart of the Ga2O3 / Ti3C2Tx sensor preparation method of the present invention is shown.

[0024] Figure 2 SEM images of Ti3C2Tx materials are shown.

[0025] Figure 3 A SEM image of Ga2O3 material is shown.

[0026] Figure 4 A SEM image of Ga2O3 / Ti3C2Tx material at a resolution of 2 μm is shown.

[0027] Figure 5 A SEM image of Ga2O3 / Ti3C2Tx material at a resolution of 1 μm is shown.

[0028] Figure 6 TEM and HRTEM images of Ti3C2Tx material are shown.

[0029] Figure 7 TEM and HRTEM images of Ga2O3 material are shown.

[0030] Figure 8 TEM and HRTEM images of Ga2O3 / Ti3C2Tx materials are shown.

[0031] Fig. 9 Elemental mapping of Ga2O3 / Ti3C2Tx material is shown.

[0032] Fig.10 The xrd patterns of Ga2O3, Ti3C2Tx and Ga2O3 / Ti3C2Tx are shown.

[0033] Fig.11 Ga 2p spectrum is shown.

[0034] Fig.12 Ga 3d spectrum is shown.

[0035] Fig.13 The O1s spectrum is shown.

[0036] Fig.14 Ti 2p spectrum is shown.

[0037] Fig.15 The C1s spectrum is shown.

[0038] Fig.16 Shown is the charge density diagram of MXene after NH3 molecule adsorption.

[0039] Fig.17 Shown is the charge density diagram of Ga2O3 after adsorption of NH3 molecules.

[0040] Fig.18 Shown is the charge density diagram of Ga2O3 / MXene after adsorption of NH3 molecules.

[0041] Fig.19 The TDOS diagrams of MXene, Ga2O3 and Ga2O3 / MXene systems after NH3 molecule adsorption are shown.

[0042] Fig. 20The TDOS diagram of Ga2O3 / MXene material before and after NH3 molecule adsorption is shown.

[0043] Fig.21 The PDOS diagram of NH3 molecules adsorbed on Ga2O3 / MXene material is shown.

[0044] Fig. 22 The resistance curves of Ga2O3 / Ti3C2Tx sensor under different NH3 concentrations are shown.

[0045] Fig.23 The resistance curve of Ga2O3 sensor at different NH3 concentrations is shown.

[0046] Fig.24 The response curves of Ga2O3 and Ga2O3 / Ti3C2Tx sensors at different NH3 concentrations are shown.

[0047] Fig.25 The fitting curves of the responses of Ga2O3 and Ga2O3 / Ti3C2Tx sensors at different NH3 concentrations are shown.

[0048] Fig.26 The response / recovery time of Ga2O3 and Ga2O3 / Ti3C2Tx sensors at 2ppm is shown.

[0049] Fig. 27 The fitting curves of the responses of Ga2O3 and Ga2O3 / Ti3C2Tx sensors at different NH3 concentrations are shown.

[0050] Fig.28 The fitting curves of the response of the Ga2O3 / Ti3C2Tx sensor under different humidity are shown.

[0051] Fig.29 The response diagram of Ga2O3 / Ti3C2Tx sensor to different gases is shown.

[0052] Fig.30 A repeatability plot of the Ga2O3 / Ti3C2Tx sensor is shown.

[0053] Fig.31 The stability curve of Ga2O3 / Ti3C2Tx sensor under different NH3 concentrations is shown.

[0054] Fig.32 A diagram showing the synergistic effect of binary nanomaterials.

[0055] Fig.33 A stereogram of TENG is shown.

[0056] Fig.34 The front view of TENG is shown.

[0057] Fig.35 A schematic diagram of the working principle of TENG is shown.

[0058] Fig.36 The voltage curves of TENG at different rotation speeds are shown.

[0059] Fig.37 The current curves of TENG at different rotation speeds are shown.

[0060] Fig.38 A detailed graph of the voltage of the TENG at a rotation speed of 50 rpm is shown.

[0061] Fig.39 The graph shows the change of the peak power of TENG with the resistance value of the external load.

[0062] Fig.40 The voltage curve of TENG charging a 330 μF capacitor is shown.

[0063] Fig.41 A voltage durability curve of TENG is shown.

[0064] Fig.42 The voltage variation curve of the Ga2O3 / Ti3C2Tx sensor powered by TENG under different NH3 concentrations is shown. DETAILED DESCRIPTION

[0065] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0066] A self-powered ammonia monitoring system comprises: a TENG, a rectification and voltage reduction module, an energy storage capacitor, a voltage management unit, a microcontroller unit (MCU), a Ga2O3 / Ti3C2Tx sensor, a wireless transmission module and a display module. The alternating current (AC) generated by the TENG is converted into direct current (DC) by the rectification and voltage reduction module and stored in the energy storage capacitor. When the capacitor voltage reaches a set value, the voltage management unit transmits the electric energy stored in the energy storage capacitor to the microcontroller unit (MCU), the Ga2O3 / Ti3C2Tx sensor, the wireless transmission module and the display module. The ammonia concentration collected by the Ga2O3 / Ti3C2Tx sensor is processed by the microcontroller unit (MCU) and then transmitted to the display module through the wireless transmission module. The display module displays the ammonia concentration.

[0067] Specifically, Figure 1As shown, the preparation process of Ga2O3 / Ti3C2Tx sensor includes preparing Ga2O3 powder, which specifically includes the following steps: S1, 0.1 mol Ga(NO3)3·xH2O was dissolved in 320 ml distilled water and stirred evenly by a magnetic stirrer, then NH4OH was added and the pH value was adjusted to 9.

[0068] S2, adding the solution obtained in step S1 into a high-pressure reactor and heating it in a muffle furnace at 100° C. for 5 hours; after the reactor is naturally cooled to room temperature, washing the obtained white precipitate with distilled water and ethanol for several times.

[0069] S3, the washed precipitate was dispersed in 5 ml of distilled water and dried in a hot air oven at 75° C. for 8 h.

[0070] S4, placing the obtained pure GaOOH powder sample in a tube furnace and calcining it at 1000°C for 5 h to obtain white Ga2O3 powder.

[0071] Specifically, the Ga2O3 / Ti3C2Tx sensor preparation process also includes etching Ti3AlC2 MAX with a mixed solution of hydrochloric acid HCl and lithium fluoride LiF to obtain Ti3C2Tx, which specifically includes the following steps: S5, 2 g of LiF and 40 mL of 9 mol HCl were mixed in a PTEF beaker and stirred at 400 rpm for 30 minutes.

[0072] S6, add 2g Ti3AlC2 to the etching solution, then place it in an ice bath for 5min, take the reaction mixture out of the ice bath, reaction temperature 35°C, reaction time 24h, centrifuge at 3500rpm for 10min to obtain a precipitate.

[0073] S7, repeatedly wash the precipitate with deionized water until the pH value of the supernatant after centrifugation is 5.

[0074] S8, adding ethanol and Ga2O3 powder 3 times the mass of Ti3C2Tx to the reaction precipitate, using the dispersion for ultrasonic treatment for 1 hour, centrifuging at 10000 rpm for 10 minutes, and then using deionized water for ultrasonic treatment for 20 minutes to obtain the precipitate.

[0075] S9, 1 ml of the supernatant was filtered with a polyvinylidene fluoride (PVDF) membrane and vacuum dried in a vacuum drying oven at 80° C. for 8 h to obtain the composite Ga2O3 / Ti3C2Tx.

[0076] Specifically, the Ga2O3 / Ti3C2Tx sensor preparation process also includes the following steps: S10, the Ga2O3 / Ti3C2Tx solution was dropped onto the FR4 substrate, a sensing film was formed by interdigital electrode IDE, and then the Ga2O3 / Ti3C2Tx sensor was obtained after vacuum drying at 60 °C for 4 h.

[0077] Scanning electron microscopy (SEM, MERLIN COMPACT) was used to characterize the surface morphology of Ti3C2Tx, Ga2O3 and Ga2O3 / Ti3C2Tx composites. Figure 2 It can be seen that the etched Ti3C2Tx nanosheets present an accordion-like layered structure. This multi-layered sheet structure has a large lateral size and a large adsorption surface area. Figure 3 It shows that the prepared Ga2O3 material is rod-shaped. Figure 4 As shown in Figure 2, in the Ga2O3 / Ti3C2Tx composite material, Ga2O3 nanorods are interlaced in the Ti3C2Tx nanosheets. Figure 5 As shown in the enlarged SEM image, the Ga2O3 nanorods on the Ti3C2Tx multilayer nanosheets can be more clearly seen. Similarly, a clear layered structure can be seen from the TEM image of the Ti3C2Tx material. Figure 6 As shown, the HRTEM image shows that the interlayer spacing d is lattice, corresponding to the 002 plane of Ti3C2Tx. Figure 7 The TEM and HRTEM images of Ga2O3 / Ti3C2Tx composite materials are shown in Figure 1. Figure 8 As shown, the nanocomposite has a high degree of crystallinity. Fig. 9 From the element mapping of the Ga2O3 / Ti3C2Tx composite material, it can be seen that Ti, Al, Ga and O elements are uniformly distributed in the material, which indicates the successful preparation of the Ga2O3 / Ti3C2Tx composite material.

[0078] The Ga2O3, Ti3C2Tx and Ga2O3 / Ti3C2Tx samples were characterized by X-ray diffraction (XRD). Fig.10 As shown. The X-ray diffractometer used is D8 ADVANCE. The radiation used by the X-ray diffractometer is Cu Kα radiation. Many diffraction peaks can be seen from the diffraction peaks of Ga2O3 and Ti3C2Tx materials in the scanning range of 15° to 80°, which matches the standard pattern (JCPDS#00-041-1103). The XRD spectrum of Ga2O3 / Ti3C2Tx contains all the diffraction peaks of pure Ga2O3 and pure Ti3C2Tx materials, further proving the existence of Ga2O3 and Ti3C2Tx. In order to further analyze the elemental composition of Ga2O3 / Ti3C2Tx composite materials, XPS characterization was performed, such as Figure 11-15 As shown. Fig.11 The XPS spectrum of Ga 2p shows two main peaks at 1118.2 eV and 1145.1 eV, corresponding to Ga 2p 3 / 2 and Ga 2p 1 / 2 The spin-orbit splitting energy level is consistent with the reported Ga 3 + The binding energy values ​​corresponding to the oxidation state are consistent. Fig.12 The Ga3d peak in the graph is composed of three components, namely the Ga-O bond at 20.3eV, the Ga-Ga bond at 20.0eV and the O2s peak at 23.8eV. Fig.13 The O1s peak in the graph is composed of two parts: the O-Ga bond at 531.3 eV and the OH bond at 533.3 eV. From the Ti 2p spectrum from 452 eV to 468 eV, it can be seen that the XPS peak of Ti 2p is composed of small peaks corresponding to six bonds, namely C-Ti-F, C-Ti-O, C-Ti-C, Ti-O, and C-Ti-O. Fig.14 The XPS scan of C 1s is shown in Fig.15 As shown, three chemical states can be identified. In addition to the chemical bonds between C and Ti, there are also CC bonds and CO bonds. They are at 282.0eV, 284.8eV and 288.3eV respectively. In the overall XPS spectrum of Ga2O3 / Ti3C2Tx composite materials, the peaks of O, Ti, C and Ga can be clearly seen, which also proves the successful synthesis of Ga2O3 / Ti3C2Tx materials, such as Fig.10 shown.

[0079] In order to further verify the feasibility of Ga2O3 / MXene composites as ammonia sensitive materials, we used density functional theory (DFT) for geometry optimization calculations. The comparative absorption of NH3 by Ga2O3, MXene and Ga2O3 / MXene was analyzed using geometry optimization calculations. These calculations were performed using the DMol3 code included in the Materials Studio 8.0 software package. The molecular model diagram of NH3 adsorbed on the surface of Ga2O3, MXene and Ga2O3 / MXene was obtained through modeling. The simplified structure of Ga2O3 / MXene was obtained by plane cutting operation. The charge density diagrams of Ga2O3, MXene and Ga2O3 / MXen adsorbing NH3 are shown in Figure 2. Figure 16-18 As shown. MXene materials have a low affinity for NH3. In contrast, Ga2O3 and Ga2O3 / MXene show stronger chemical bonds with NH3. Compared with the Ga2O3 system, the charge transfer in the Ga2O3 / MXene system shows stronger intensity. By optimizing the geometric parameters, the optimal bond angle and length of NH3 are obtained. The adsorption energy of the material is calculated using the following formula: E ad =E gas / sub -E sub -E gas (1); Among them, E gas / sub is the energy of the entire system; E sub is the energy of Ga2O3, MXene and Ga2O3 / MXene; E gas is the energy of the NH3 molecule.

[0080] As shown in Table 1, the adsorption energy (Ea d ) is -1.361eV, which exceeds that of MXene and Ga2O3. Therefore, compared with MXene and Ga2O3, Ga2O3 / MXene nanocomposites exhibit better NH3 adsorption capacity.

[0081] Table 1 Parameters of Ga2O3, MXene and Ga2O3 / MXene adsorption systems

[0082] The total density of states (TDOS) and projected density of states (PDOS) of MXene, Ga2O3, and Ga2O3 / MXene were analyzed to reveal the electronic structures. Fig.19 As shown in the TDOS diagram, the electron density curve of Ga2O3 / MXene moves to the left compared with Ga2O3, which is due to the effect of MXene doping. Fig. 20As shown in Figure 1, the peak in the TDOS graph is slightly enhanced. Fig.21 As shown in Figure 2, the TDOS changes of Ga2O3 / MXene materials are mainly attributed to the interaction between Ti 3d orbital, Ga 3d, C 1s orbital and O 2p orbital. These orbitals have obvious overlapping peaks at -19.7eV, 2.7eV and -4.3eV, which indicates that there is a strong hybridization between NH3 molecules and Ga2O3 / MXene nanocomposites.

[0083] The sensor was placed in different NH3 concentration environments from 0.5ppm to 3ppm in sequence. After the sensor's resistance stabilized at each NH3 concentration, it was placed in 0ppm ammonia to restore its resistance. After the resistance returned to the initial value, it was placed in the next concentration of NH3 for testing. Fig. 22 and Fig.23 The resistance changes of Ga2O3 / Ti3C2Tx composite materials and sensors based on pure Ga2O3 materials at different NH3 concentrations of 0.5ppm-3ppm are shown respectively. The resistance of the sensor increases with the increase of NH3 concentration. The resistance of Ga2O3 and Ga2O3 / Ti3C2Tx sensors at 0ppm are approximately 5GΩ and 100MΩ, respectively, which indicates that the doping of Ti3C2Tx reduces the resistance of the sensor. The sensor with reduced resistance is more conducive to adapting to the circuit for monitoring. In order to better quantify and compare the performance of the sensor, the resistance of the sensor is converted into response. The responses of Ga2O3 and Ga2O3 / Ti3C2Tx sensors at different NH3 concentrations are shown in Figure 2. Fig.24 As shown. It can be seen that the response of the Ga2O3 / Ti3C2Tx sensor is higher than that of the Ga2O3 sensor, which indicates that the composite material has a better ammonia sensing effect. The calculation method of the response S is as follows: Among them, R g It is the resistance of the sensor under a certain concentration of NH3. a is the resistance of the sensor in 0ppm ammonia. The fitting curves of Ga2O3 and Ga2O3 / Ti3C2Tx sensors show that the response of the sensor gradually increases with the increase of NH3 concentration. Fig.25 , their fitting formulas are Y = 167.8-176.3*0.85X and Y = 92.3-103.3*0.49X, which provide guidance for NH3 sensing. Their fitting coefficients R2 are all above 0.95, indicating that the fitting formulas are very accurate.

[0084] Fig.26The response / recovery curves of Ga2O3 and Ga2O3 / Ti3C2Tx sensors at 2ppm NH3 concentration are shown. The response / recovery time refers to the time taken for the response value to rise from a stable response value to 90%, and the time taken for the stable response value to drop to 10%, respectively. As can be seen from the figure, the response times of Ga2O3 and Ga2O3 / Ti3C2Tx sensors are 4s and 5s, respectively. The recovery time of Ga2O3 / Ti3C2Tx sensor is 28s, which is higher than 39s of pure Ga2O3 sensor. In addition, Table 1 lists the sensing performance of Ga2O3 and Ga2O3 / Ti3C2Tx sensors. As can be seen from the results, Ga2O3 / Ti3C2Tx sensor has a better response value.

[0085] Fig. 27 The resistance curve of Ga2O3 / Ti3C2Tx sensor at room temperature (at 0ppm) is shown. It can be seen that as the temperature gradually increases from 15℃ to 29℃, the resistance value of the sensor increases linearly. However, the effect of temperature on the resistance value is not significant, which indicates that temperature fluctuations under room temperature conditions have almost no effect on sensing. In order to explore the interference of humidity on Ga2O3 / Ti3C2Tx sensor, the response of the sensor in the range of 0% relative humidity (RH) to 97% RH was tested, as shown in Figure 2. Fig.28 As shown. The response of the Ga2O3 / Ti3C2Tx sensor is linear with the increase of humidity, and the fitting curve is Y=0.1826+0.0709X. In the actual ammonia monitoring scenario, based on the influence curve of humidity and temperature, more accurate ammonia sensing data can be obtained by calibrating the temperature and humidity sensor. Among them, different saturated salt solutions are used to simulate the humidity test environment of the gas sensor. The specific configuration process of the humidity test environment is: the corresponding humidity of lithium chloride (LiCl), potassium acetate (CH3COOK), magnesium chloride (MgCl2), potassium carbonate (K2CO3), magnesium nitrate (Mg(NO3)2), copper chloride (CuCl2), sodium chloride (NaCl), potassium chloride (KCl) and potassium sulfate (K2SO4) saturated salt solutions are 11%, 23%, 33%, 43%, 52%, 67%, 75%, 85% and 97%RH respectively. Phosphorus pentoxide (P2O5) powder is used as a desiccant to provide a dry detection environment (0%RH) for the humidity sensor.

[0086] Fig.29 The selectivity of Ga2O3 / Ti3C2Tx thin film sensor to 1ppm acetone, nitrogen dioxide, hydrogen sulfide, sulfur dioxide, carbon monoxide and NH3 gases is shown. The experimental results show that the response of Ga2O3 / Ti3C2Tx sensor to NH3 is much higher than that of other gases. Fig.30The repeatability measurement results of Ga2O3 / Ti3C2Tx sensor at different NH3 concentrations are shown. The response value of Ga2O3 / Ti3C2Tx sensor was repeatedly measured in an environment with 1ppm NH3 concentration. The results show that the sensor response value of the same concentration does not change much in repeated experiments, indicating that Ga2O3 / Ti3C2Tx sensor has good repeatability for different concentrations of NH3.

[0087] At the same time, the long-term stability of Ga2O3 / Ti3C2Tx sensors was tested, such as Fig.31 As shown. The response of the sensor was measured every 10 days at NH3 concentrations of 0.5ppm, 1.5ppm, and 3ppm. It can be seen that the response deviation of the Ga2O3 / Ti3C2Tx sensor at different NH3 concentrations is less than 5% as time increases, indicating its excellent long-term stability.

[0088] The above experimental results show that Ga2O3 / Ti3C2Tx composite materials have excellent sensitivity to NH3. The sensing mechanism mainly comes from the synergistic effect of binary nanomaterials. Fig.32 The synergistic effect of binary nanomaterials is shown. The multilayered nanostructure of Ti3C2Tx has the advantage of a large specific surface area, which can increase its contact sites with Ga2O3, provide a large number of adsorption sites for NH3, and effectively improve the response of the composite material to NH3. In addition, the reduction in sensor resistance in NH3 may be related to the improvement of the connectivity of the nanocomposite after Ga2O3 adsorbs NH3 molecules.

[0089] Specifically, TENG is cylindrical and includes a stator and a rotor. The diameter of the cylindrical rotor is smaller than that of the cylindrical stator, and the stator is sleeved on the outside of the rotor, and the rotor rotates relative to the stator.

[0090] Specifically, the rotor includes: a first acrylic shell, a finger electrode covering the outer side of the first acrylic shell and a Capton film covering the finger electrode, the finger electrode is covered with the Capton film as a friction electric layer, and the finger electrode includes: a plurality of first copper electrode layers and a plurality of second copper electrode layers, the first copper electrode layer and the second copper electrode layer are crossed to form the finger electrode, and the first copper electrode layer and the second copper electrode layer extend along the length direction of the acrylic shell.

[0091] Specifically, the stator includes: a second acrylic shell and multiple grid-shaped copper electrodes covering the inner surface of the second acrylic. The stator has multiple copper electrodes, and two adjacent copper electrodes on the stator are spaced a certain distance apart to form a grid-shaped copper electrode. The copper electrodes on the stator extend along the length direction of the second acrylic shell.

[0092] Specifically, there are six copper electrodes on the first copper electrode layer, the second copper electrode layer and the stator.

[0093] Specifically, in the initial state, the copper electrode on the stator is aligned with the copper electrode on the left side of the rotor; due to the difference in electronegativity, electrons are transferred from the surface of the copper electrode on the stator to the surface of the Capton film, and equal amounts of positive and negative charges are generated on the copper electrode on the stator and the surface of the Capton film, respectively. At this time, the TENG is in an electrostatic equilibrium state, and no free electrons flow through the external circuit; as the rotor rotates, the overlapping area between the copper electrode on the stator and the copper electrode on the left side of the rotor decreases, and the potential difference drives the current from the copper electrode on the right side of the rotor to the copper electrode on the left side of the rotor, thereby achieving a new electrostatic equilibrium, as shown in Figure 2. Fig.35 As shown in II. Fig.35 As shown in Figure III, the charge transfer process will continue until the copper electrode on the stator is completely aligned with the copper electrode on the right side of the rotor, at which time the current in the circuit is 0; when the rotor continues to rotate, the overlapping area between the copper electrode on the stator and the copper electrode on the left side of the rotor gradually increases, as shown in Figure III. Fig.35 As shown in IV in , a reverse current is generated until the top copper electrode is completely aligned with the left electrode, thereby generating an AC current signal.

[0094] Fig.33 and Fig.34 The basic structure of TENG is shown in Figure 1. TENG adopts a free-standing structure of a rotor and a stator. The diameters of the rotor and stator are 8 cm and 9 cm respectively. The length of the barrel is 15 cm. The barrel-shaped rotor is attached with a grid-structured copper electrode, and the copper electrode is covered with a Capton film as a triboelectric layer. For the stator, six grid-shaped copper electrodes are covered on the inner surface of the barrel-shaped acrylic. The working principle of TENG is as follows Fig.35 As shown, the principle is based on the coupling of contact electrification and electrostatic induction.

[0095] The power generation performance of TENG was tested. Fig.36 As shown in Figure 2, when the rotation speed of TENG gradually increases from 10 revolutions per minute (rpm) to 70 rpm, the output voltage gradually increases. This is attributed to the rapid induction and transfer of charges under high-frequency contact. Similarly, as the short-circuit current of TENG gradually increases with the increase of rotation speed, as shown in Figure 2 Fig.37 , in the range of 10-50rpm, the current and speed are almost linearly related. When the speed continues to increase, the current growth rate slows down. Fig.38 The open circuit voltage of TENG at 50 rpm is shown. It can be seen that the electrical output of TENG is a periodic alternating current. When the load resistance is 700 MΩ, the output power of TENG reaches a maximum value of 9.1 mW. Fig.39The voltage curve of TENG charging a 330μF capacitor at a speed of 50rpm after rectification and voltage drop resistor management is shown in the figure below. Fig.40 As shown. After 250s of charging, the voltage of the capacitor can reach 15V. In order to test the stability of TENG's electrical output, TENG was subjected to a 2-hour durability test. Fig.41 As shown. Fig.41 As can be seen in the figure, after 2 hours of testing, the open circuit voltage of TENG has hardly changed. After the TENG performance test is completed, TENG is used to directly power the Ga2O3 / Ti3C2Tx ammonia sensor. When the sensor switches between 0ppm and 3ppm ammonia environments, the voltage value on the sensor changes. This provides a solution for self-powered ammonia sensing, such as Fig.42 shown.

[0096] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A self-powered ammonia monitoring system, characterized in that: include: TENG, rectification and step-down module, energy storage capacitor, voltage management unit, microcontroller unit MCU, Ga2O3 / Ti3C2Tx sensor, wireless transmission module and display module; through the rectification and step-down module, the alternating current generated by TENG is converted into direct current and stored in the energy storage capacitor. When the capacitor voltage reaches the set value, the voltage management unit transmits the electric energy stored in the energy storage capacitor to the microcontroller unit MCU, Ga2O3 / Ti3C2Tx sensor, wireless transmission module and display module. The ammonia concentration collected by the Ga2O3 / Ti3C2Tx sensor is processed by the microcontroller unit MCU and then transmitted to the display module through the wireless transmission module. The display module displays the ammonia concentration.

2. A self-powered ammonia monitoring system according to claim 1, characterized in that: The preparation process of Ga2O3 / Ti3C2Tx sensor includes preparing Ga2O3 powder, which specifically includes the following steps: S1, 0.1 mol Ga(NO3)3·xH2O was dissolved in 320 ml distilled water and stirred evenly by a magnetic stirrer, then NH4OH was added and the pH value was adjusted to 9; S2, adding the solution obtained in step S1 into a high-pressure reactor and heating it in a muffle furnace at a temperature of 100° C. for 5 hours; after the reactor is naturally cooled to room temperature, washing the obtained white precipitate with distilled water and ethanol several times respectively; S3, disperse the washed precipitate in 5 ml of distilled water and dry it in a hot air oven at 75 °C for 8 h; S4, placing the obtained pure GaOOH powder sample in a tube furnace and calcining it at 1000°C for 5 h to obtain white Ga2O3 powder.

3. A self-powered ammonia monitoring system according to claim 2, characterized in that: The preparation process of the Ga2O3 / Ti3C2Tx sensor also includes etching Ti3AlC2 MAX with a mixed solution of hydrochloric acid HCl and lithium fluoride LiF to obtain Ti3C2Tx, which specifically includes the following steps: S5, 2 g LiF and 40 mL 9 mol HCl were mixed in a PTEF beaker and stirred at 400 rpm for 30 min; S6, adding 2 g of Ti3AlC2 to the etching solution, then placing it in an ice bath for 5 min, taking the reaction mixture out of the ice bath, reaction temperature 35 ° C, reaction time 24 h, centrifuging at 3500 rpm for 10 min to obtain a precipitate; S7, repeatedly washing the precipitate with deionized water until the pH value of the supernatant after centrifugation is 5; S8, adding ethanol and Ga2O3 powder 3 times the mass of Ti3C2Tx to the reaction precipitate, using the dispersion for ultrasonic treatment for 1 hour, centrifuging at 10000 rpm for 10 minutes, and then using deionized water for ultrasonic treatment for 20 minutes to obtain the precipitate; S9, 1 ml of the supernatant was filtered with a polyvinylidene fluoride (PVDF) membrane and vacuum dried in a vacuum drying oven at 80° C. for 8 h to obtain the composite Ga2O3 / Ti3C2Tx.

4. A self-powered ammonia monitoring system according to claim 3, characterized in that: The Ga2O3 / Ti3C2Tx sensor preparation process also includes the following steps: S10, the Ga2O3 / Ti3C2Tx solution was dropped onto the FR4 substrate, a sensing film was formed by interdigital electrode IDE, and then the Ga2O3 / Ti3C2Tx sensor was obtained after vacuum drying at 60 °C for 4 h.

5. A self-powered ammonia monitoring system according to claim 4, characterized in that: TENG is cylindrical and includes a stator and a rotor. The diameter of the cylindrical rotor is smaller than that of the cylindrical stator, and the stator is sleeved on the outside of the rotor, and the rotor rotates relative to the stator.

6. A self-powered ammonia monitoring system according to claim 5, characterized in that: The rotor includes: A first acrylic shell, a finger electrode covering the outer side of the first acrylic shell and a Capton film covering the finger electrode, the finger electrode is covered with the Capton film as a triboelectric layer, the finger electrode comprises: a plurality of first copper electrode layers and a plurality of second copper electrode layers, the first copper electrode layers and the second copper electrode layers are crossed to form the finger electrode, and the first copper electrode layers and the second copper electrode layers extend along the length direction of the acrylic shell.

7. A self-powered ammonia monitoring system according to claim 6, characterized in that: The stator includes: The second acrylic shell and multiple grid-shaped copper electrodes covering the inner surface of the second acrylic, the stator has multiple copper electrodes, two adjacent copper electrodes on the stator are spaced a certain distance apart to form a grid-shaped copper electrode, and the copper electrodes on the stator extend along the length direction of the second acrylic shell.

8. A self-powered ammonia monitoring system according to claim 7, characterized in that: There are six copper electrodes on the first copper electrode layer, the second copper electrode layer and the stator.

9. A self-powered ammonia monitoring system according to claim 8, characterized in that: In the initial state, the copper electrode on the stator is aligned with the copper electrode on the left side of the rotor; due to the difference in electronegativity, electrons are transferred from the surface of the copper electrode on the stator to the surface of the Capton film, and equal amounts of positive and negative charges are generated on the copper electrode on the stator and the surface of the Capton film, respectively. At this time, the TENG is in an electrostatic equilibrium state, and no free electrons flow through the external circuit; as the rotor rotates, the overlapping area between the copper electrode on the stator and the copper electrode on the left side of the rotor decreases, and the potential difference drives the current from the copper electrode on the right side of the rotor to the copper electrode on the left side of the rotor, thereby achieving a new electrostatic equilibrium, and the charge transfer process will continue until the copper electrode on the stator is completely aligned with the copper electrode on the right side of the rotor, at which time the current in the circuit is 0; when the rotor continues to rotate, the overlapping area between the copper electrode on the stator and the copper electrode on the left side of the rotor gradually increases, generating a reverse current until the top copper electrode is completely aligned with the left electrode, thereby generating an AC current signal.

Citation Information

Patent Citations

  • Self-driving high precision angle measuring system and method

    CN110146010A

  • Room-temperature ammonia gas sensor based on Ti3C2Tx / WO3 composite nano material, preparation method and application thereof

    CN112255278A